THE ROLE OF INDEPENDENT AND INNOVATIVE EDUCATION IN LANGUAGE LEARNING - Nasiba Saburovna Jumatova (Scholar Express Journal, 2024)
The most important and urgent task facing language education is to bring up a creative thinker, that is, a creative and independent thinker, which is necessary for our modernizing, developing and developing country. It is no exaggeration to say that the new pedagogical technologies, innovations, and new pedagogical methods that have been rapidly entering the education system in recent years have fundamentally changed the content of education. The era has come when a modern pedagogue should be a "director" rather than an "actor" in the course of the lesson
Keywords: Educational field; traditional; new pedagogical technologies; innovations